HUBUNGAN AKTIVITAS FISIK DENGAN DISMENORE PADA MAHASISWI PPTQ AL-ASY’ARIYYAH GEDUNG SYAUQUNAL QUR’AN KALIBEBER - Atika Fitriyani; Anisa Ell Raharyani; Romdiyah Romdiyah (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Background: Dysmenorrhea is a condition of severe menstrual pain that can interfere with daily activities with various symptoms felt, such as abdominal pain, cramps, back pain, nausea, diarrhea, and so on. Objective: To find out the relationship between physical activity and dysmenorrhea in students of PPTQ Al-Asy'ariyyah Syauqunal Qur'an Building Kalibeber. Methods: The type of research used is quantitative research using analytic research design with a cross sectional approach. The number of samples used was 48 respondents, with purposive sampling technique. The analysis technique used the spearman rank test. Results: there is a relationship between physical activity and dysmenorrhea in students of PPTQ Al-Asy'ariyyah Syauqunal Qur'an Kalibeber building with a p value of 0.000 <0.05 with a Correlation Coefficient value of -0.574 which means it has a relationship in the strong category. Conclusion: There is a relationship between physical activity and dysmenorrhea in students of PPTQ Al-Asy'ariyyah Syauqunal Qur'an Kalibeber building.